Interprofessional collaboration in nursing homes (interprof): development and piloting of measures to improve interprofessional collaboration and communication : a qualitative multicentre study - Müller, Christiane Annette; Hoell, Andreas; Werle, Jochen; Weyerer, Siegfried (BMC family practice, 2018)
Given both the increase of nursing home residents forecast and challenges of current interprofessional interactions, we developed and tested measures to improve collaboration and communication between nurses and general practitioners (GPs) in this setting. Our multicentre study has been funded by the German Federal Ministry of Education and Research (FK 01GY1124).